Essential oil extraction from herbs and their use in the food industry - András, Csaba; Salamon, Bernadett; György, Éva; Mihok, Emőke; Szép, Alexandru (Acta Agraria Debreceniensis, 2018)
Essential oil extraction of wild caraway and thyme was performed using a classical (HD) and microwave hydro-distillation (MWHD) and a laboratory supercritical fluid extraction (SFE) with a carbon dioxide as solvent. Our experiments demonstrated that the extraction yield of the essential oil performed in same conditions was influenced by the location of growth area; the maximum extraction yield of 10 ml 100 g-1 caraway was obtained from dried seeds collected from Csíkmadaras. This quantity far exceeded the yield of the Újtusnád samples. In the case of wild caraway (Carum carvi L.), the extraction method influenced thecomposition of the essential oil (carvone/limonene ratio), the highest limonene content being achieved by classical hydro-distillation. In the case of thyme, this effect was not detected, the thymol/carvacrol ratio was independent from the given extraction method. The obtained thyme essential oil possesses high antimicrobial activity demonstrated by agar diffusion test. The thyme extract provides a good protection against microorganisms collected on the surface of fresh vegetables following bacterial stains: Citrobacter portucalensis, Pseudomonas hunanensis, Pseudomonas baetica, Pseudomonas parafulva, Bacillus mojavensis and Enterobacter cloacae. Protective effect was also detected on the vegetable surface of by chitosan-based edible film coating during a 6-day-long storage period at a temperature of 4 °C. The caraway essential oil used as soft cheese seasoning with a direct, dilution-free method, proved to be unsuitable because the uneven distribution and confer a strong, unpleasant taste to the product in comparison with the ground wild caraway seed-dressed cheese.